BET proteins regulate homologous recombination‐mediated DNA repair: BRCAness and implications for cancer therapy. Issue 4 (4th December 2018) - Mio, Catia; Gerratana, Lorenzo; Bolis, Marco; Caponnetto, Federica; Zanello, Andrea; Barbina, Mattia; Di Loreto, Carla; Garattini, Enrico; Damante, Giuseppe; Puglisi, Fabio
Abstract : Bromodomain and Extra‐Terminal (BET) proteins are historically involved in regulating gene expression and BRD4 was recently found to be involved in DNA damage regulation. Aims of our study were to assess BRD4 regulation in homologous recombination‐mediated DNA repair and to explore novel clinical strategies through the combinations of the pharmacological induction of epigenetic BRCAness in BRCA1 wild‐type triple negative breast cancer (TNBC) cells by means of BET inhibitors and compounds already available in clinic. Performing a dual approach (chromatin immunoprecipitation and RNA interference), the direct relationship between BRD4 and BRCA1/RAD51 expression was confirmed in TNBC cells. Moreover, BRD4 pharmacological inhibition using two BET inhibitors (JQ1 and GSK525762A) induced a dose‐dependent reduction in BRCA1 and RAD51 levels and is able to hinder homologous recombination‐mediated DNA damage repair, generating a BRCAness phenotype in TNBC cells. Furthermore, BET inhibition impaired the ability of TNBC cells to overcome the increase in DNA damage after platinum salts (i.e., CDDP) exposure, leading to massive cell death, and triggered synthetic lethality when combined with PARP inhibitors (i.e., AZD2281). Altogether, the present study confirms that BET proteins directly regulate the homologous recombination pathway and their inhibition induced a BRCAness phenotype in BRCA1 wild‐type TNBC cells. Noteworthy, being this strategy based on drugs already available for human use, it is rapidly transferable and could potentially enable clinicians to exploit platinum salts and PARP inhibitors‐based treatments in a wider population of TNBC patients and not just in a specific subgroup, after validating clinical trials. Abstract : What's new? Triple negative breast cancer (TNBC) lacks a well‐defined molecular target and its molecular heterogeneity restricts treatment options. Epigenetic BRCAness has been linked to poor outcome, but its influence on platinum‐based regimens or PARP inhibitors remains uncertain. Our study explores BET proteins as a BRCAness phenotype inducer in BRCA1 wild‐type TNBC cells and evaluates its synergism with platinum salts and PARP inhibition. The results confirm the induction of BRCAness through BET inhibition and gives proof of concept that BET proteins directly regulate homologous recombination‐directed DNA repair in TNBC cells, offering the rationale to design novel pharmacological combinations using already available drugs.